2019
DOI: 10.13040/ijpsr.0975-8232.10(4).1966-71
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Biofilm is a layer like aggregates of bacterial cells which are formed on biotic and abiotic surfaces. Pseudomonas aeruginosa plays an essential role in the aggregation of bacteria on biofilm formation. Quorum sensing and extracellular polysaccharide play a vital role in the biofilm formation in P. aeruginosa. The present study was aimed to investigate the anti-biofilm effect of lyophilized extracts of Chlorella. Materials and Methods: The lyophilized aqueous and ethanolic extracts of Chlorella wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…increased the superoxide production and exerted ROS generated oxidative stress in the cytoplasm of bacterial cells, which eventually led to cell death [125]. In addition, diethyl phthalate with antimicrobial properties was reported for its ability to interfere with quorum sensing mediated virulence factors and biofilm formation in Pseudomonas aeruginosa [126,127]. Another study demonstrated that dimethyl phthalate (concentration ranged from 20 to 40 mg/L) greatly inhibited the growth and glucose utilization of Pseudomonas fluorescens, meanwhile the surface hydrophobicity and membrane permeability of P. fluorescens were also increased.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…increased the superoxide production and exerted ROS generated oxidative stress in the cytoplasm of bacterial cells, which eventually led to cell death [125]. In addition, diethyl phthalate with antimicrobial properties was reported for its ability to interfere with quorum sensing mediated virulence factors and biofilm formation in Pseudomonas aeruginosa [126,127]. Another study demonstrated that dimethyl phthalate (concentration ranged from 20 to 40 mg/L) greatly inhibited the growth and glucose utilization of Pseudomonas fluorescens, meanwhile the surface hydrophobicity and membrane permeability of P. fluorescens were also increased.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The AMR (including for immune factors of the host) of MRSA and biofilm forming bacteria, such as other Staphylococcus spp., E. coli and P. aeruginosa [ 31 ], increases to several hundred times in biofilms, mainly because of decreased drug permeability and appearance of dormant persisters [ 102 ]. The reason for the selection of MRSA for biofilm research in this study is, as we have already emphasized, MRSA biofilms are persistent, colonize catheters and other devices and are significantly lethal to patients with (necrotic) wounds [ 29 , 30 , 100 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of antineoplastic and antibacterial activity is very relevant in the present time since cancer is the second leading cause of death globally after heart disease, [ 28 ] and antimicrobial resistance (AMR), found in many species of bacteria, is an increasingly serious threat to human health. In addition, bacterial biofilms, which contribute to >80% of all infections and 65% of infections in developed countries [ 29 , 30 ], are another challenge for which some phloroglucinol derivatives [ 31 , 32 ] may provide relief. Other pharmacological effects of phloroglucinols include antioxidant, antidepressant, antiviral (including effectiveness against SARS-CoV-19), antinociceptive etc.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the McFarland turbidity standard is to adjust the turbidity of the suspension liquid such that the number of bacteria is within the defined range. The standard level of 0.5 McFarland is 1.5 × 10 8 bacterial cells per mL (Gayatri et al 2019).…”
Section: Bacteria Preparationmentioning
confidence: 99%
“…Using a disposable 6-in Onemed cotton swab, bacteria from the agar medium were collected and placed in a test tube with Aqua Dest (distilled water). After the solution had become homogenous, its turbidity color was adjusted to the 0.5 McFarland standard as outlined in Gayatri et al (2019). After the same turbidity was obtained, the solution was ready for the spraying procedure over the surgical mask.…”
Section: Bacteria Preparationmentioning
confidence: 99%